Medically unexplained somatic complaints: management in real life - Syed, Sifat E (Bangladesh Journal of Medicine, 2023)
Medically unexplained somatic complaints (MUSC) are a common phenomenon in primary care settings, and they pose a challenge to clinicians in terms of diagnosis and management. MUSC refers to the presence of physical symptoms that are not attributed to any known medical or organic cause. These symptoms can significantly affect patients’ quality of life and impose a substantial burden on healthcare systems. In real-life clinical practice, managing MUSC requires a multifaceted approach that includes a thorough clinical evaluation, psychoeducation, and collaborative care. The management of MUSC should start with establishing a good rapport with the patient and understanding their concerns and beliefs about their symptoms. Clinicians should also rule out any underlying medical conditions that may contribute to the symptoms. Once medical causes are excluded, the focus should shift to addressing the psychosocial factors that may be contributing to the symptoms. This can include educating patients about the nature of MUSC and the role of stress and anxiety in exacerbating their symptoms. Collaborative care involving primary care clinicians, mental health professionals, and other specialists is an effective approach for managing MUSC. It is essential to tailor the treatment to the individual needs of the patient and to ensure that they are engaged and motivated to participate in their care. In conclusion, managing MUSC in real-life clinical practice requires a collaborative, patient-centered approach that addresses the physical, psychological, and social factors contributing to the symptoms. Clinicians should adopt a biopsychosocial model of care and that maximizes patient engagement and improves their quality of life. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 184